Amyloid β binding proteins in vitro and in normal human cerebrospinal fluid - Adam A. Golabek; Marcos A. Marques; Maciej Łałowski; Thomas Wısnıewskı (1995)
A major neuropathological feature of Alzheimer's disease (AD) is the deposition of amyloid β (Aβ) in the form of senile plaques. The Aβ peptide exists both in a β-pleated sheet fibrillar form in amyloid deposits and as a normal soluble protein in biological fluids. Numerous proteins have been identified immunohistochemically to be associated with senile plaques, where Aβ is the major constituent. Some of the latter have also been suggested to be carrier of the normal soluble Aβ (sAβ) including apolipoprotein J (apoJ), apolipoprotein E (apoE) and transthyretin (TTR). We have found, using several different methods, that numerous proteins can bind synthetic Aβ peptides when high concentrations are used; however, using an affinity anti-sAβ column we confirm that apoJ is the major binding protein in pooled human cerebrospinal fluid. On the other hand it is known that apoE co-purifies with Aβ biochemically extracted from senile plaques. In AD tissue there may be a change in the major apolipoprotein binding Aβ from apoJ to apoE.